A Simple Visual Ethanol Biosensor Based on Alcohol Oxidase Immobilized onto Polyaniline Film for Halal Verification of Fermented Beverage Samples - Kuswandi, B; Irmawati, T; Hidayat, MA; Jayus; Ahmad, M (MDPI, 2024)
Indexed by WOS